Key Audit Matters: Atribut Kantor Akuntan Publik, Keterbacaan, dan Reaksi Investor - Deddy Kurniawansyah; Iswajuni Iswajuni; Nawa Iftitah (Studi Akuntansi dan Keuangan Indonesia, 2026)
This study aimed to examine the effect of the Big four accounting firms, audit fees, and audit partner gender on the readability of Key Audit Matters (KAM) and its impact on investor reactions in Indonesian companies. The population of this study is all companies listed on the Indonesia Stock Exchange (IDX) period 2022-2024. The sample was selected using a census method with a total of 1,894 observations. Data analysis techniques used multiple regression with the help of SmartPLS. This study found that the involvement of the Big four accounting firms, audit fees, and audit partner gender had no effect on the readability of KAM. Investors in Indonesia reacted positively to the easy-to-read KAM. This study showed a significant contribution to agency and signaling theory as an important form of information quality that can minimize information asymmetry problems with the presentation of well-readable KAM. For investors, it can improve their understanding of accounting practices, reporting practices, and corporate governance issues that impact decision making. For regulators, it can be a strategy to formulate policies that can improve the value of auditor report communications in Indonesia.